Efektivitas Penggunaan Media Papan Bilangan terhadap Kemampuan Berhitung Perkalian Bilangan Bulat pada Siswa - Ulfa, Safareni; Khatimah, Husnul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to determine the effectiveness of the use of the number board method in improving the multiplication skills of grade III students at SD Negeri 6 Tangan-Tangan. The research method used was an experiment with a sample of 15 grade 3 students. The data collection techniques used were pre-test and post-test, and data analysis was carried out using the Paired Sample Test to compare the differences in scores before and after the intervention. The post-test results showed a significant increase in students' scores in mastering multiplication material after the application of the number board method. From the results of the study, it can be concluded that the use of the number board method significantly improves students' abilities in multiplication material at SD Negeri 6 Tangan-Tangan. Keywords: Effectiveness, Number Board, Multiplication, Whole Numbers